SYNTHESISAND PHYSICAL-CHEMICAL PROPERTIES OF 8-AMINO-7-(2-HYDROXY-3-i-PROPOXYPROPYL-1)-3-METHYLXANTHINES - M. I. Romanenko; M. V. Nazarenko; D. G. Ivanchenko; O. A. Pakhomova; A. Yu. Cherchesova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Introduction